Pediatric Urology Patients With Megaureter May Have a Risk of Contracting Crohn Disease. Issue 2 (February 2015) - Kolho, Kaija-Leena; Taskinen, Seppo; Rintala, Risto J.
Abstract : ABSTRACT: Crohn disease (CD) may develop at any age, but is most typically diagnosed in late adolescence and early adulthood. To the best of our knowledge, there are no reports showing that congenital urological abnormalities may be associated to CD. We describe 5 pediatric patients who had ureteral/urethral abnormalities in their infancy and developed CD during subsequent years. The occurrence of CD in these patients constitutes a novel potential association.